PENYAJIAN MUSIK SEBAGAI DAYA TARIK MINAT WISATAWAN DI LOKASI OBJEK WISATA LUMBAN SILINTONG DESA LUMBAN SILINTONG KECAMATAN BALIGE KABUPATEN TOBASA - Nova R. Simamora (Universitas Negeri Medan, 2013)
The results of this study indicate that the presented music brings an important role in attracting tourists to visit Lumban Silintong although the music is not the main attraction at this attraction but music has been a contributing factor in the development of its tourism industry. As for the presentation of musical elements that exist in Lumban Silintong ie musical instruments, where the instruments used are the keyboard but once there is a guitar and flute. Music players, coming from people around Lumban Silintong. Music, usually served there generally is pop music, dangdut, and House music, a song is usually sung pop songs and Indonesian Batak, old song and song House music dangdut whereas normally served starting at 11 pm. Visitors, the tourists who come to Lumban Silintong, stopped at a cafe to enjoy a meal while enjoying the view of Lake Toba. Time and place penellitian, music usually presented on Saturdays, Sundays and holidays, while his place is at a floating cafe built on the lake or on the lake. Travelers interested in the presentation of the music made in Lumban Silintong cafe where music becomes a means of entertainment for tourists and can also as a means of expression. Government efforts to improve the attraction Lumban Silintong not fully support, the government is still lacking in development to promote attractions Lumban Silintong